2018
DOI: 10.1111/iej.13031
|View full text |Cite
|
Sign up to set email alerts
|

Microguided Endodontics: a case report of a maxillary lateral incisor with pulp canal obliteration and apical periodontitis

Abstract: Aim To describe a minimally invasive method to create a 3D‐printed guide to gain access to obliterated root canals on the basis of CBCT data. Summary A 85‐year‐old female ASA III was referred for root canal treatment of tooth 22. Clinically, there were no complaints, no percussion pain or sinus tract. Radiologically, the tooth had an obliterated canal with an apical radiolucency. The tooth was diagnosed with asymptomatic apical periodontitis. Microguided Endodontic treatment was performed with the help of a 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 30 publications
(81 reference statements)
0
40
0
12
Order By: Relevance
“…The benefits of guided access cavity preparation include conservative access cavity preparation, decreased chair time and reduced risk of iatrogenic damage (Torres et al . , Connert et al . ).…”
Section: Assessment Of Root Canal Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of guided access cavity preparation include conservative access cavity preparation, decreased chair time and reduced risk of iatrogenic damage (Torres et al . , Connert et al . ).…”
Section: Assessment Of Root Canal Anatomymentioning
confidence: 99%
“…Stents with guide sleeves have been 3D printed from optical surface scans and CBCT data sets to allow guided access cavity preparation (Connert et al 2019). The benefits of guided access cavity preparation include conservative access cavity preparation, decreased chair time and reduced risk of iatrogenic damage (Torres et al 2018, Connert et al 2019).…”
Section: Assessment Of Root Canal Anatomymentioning
confidence: 99%
“…From Torres et al (2019) – ‘The CBCT revealed a calcified root canal up to the apical third of the root and an apical radiolucency of 39.8 mm 3 , and the buccal bone plate was preserved.…”
Section: The Price 2020 Explanation and Elaboration Documentmentioning
confidence: 99%
“…Nonetheless, cleaning and restoration with sub-gingival margins is difficult so that it would augment the developing periodontitis and loss of the tooth's attachment. [135][136][137] Hence, it is necessary to develop a bio-active Class V composite for eliminating secondary caries and root caries.…”
Section: Nano-materials For Endodonticsmentioning
confidence: 99%